Digital Construction Implementation in the Era of Industrial Revolution 4.0 Using Augmented Reality Technology to Determine Building Coordinates - Arif Widayanto; A Antonius; Moh Faiqun Niam (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
The Industry revolution 4.0 has become a prominent topic of discussion, emphasizing the need to harness digital technology to enhance various aspects of human work, including the construction industry. In the field of construction, Building Information Modeling (BIM) has been widely adopted as a guiding framework for construction processes. Additionally, Augmented Reality (AR) technology has emerged as a powerful tool for bringing 3D models into the physical world. This research employs a qualitative approach, utilizing 3D design data of Pile Caps in the construction of the IKN Minister's Residence and Solo - Yogyakarta Toll Road Office. A total of 74 and 68 coordinate points were extracted from each design to analyze the discrepancies resulting from the implementation of AR technology. The findings reveal that both designs exhibited a margin of error of 0.6148648649 % for the IKN Minister's Residence and 0.6102941177 % for the Solo - Yogyakarta Toll Road Office, both of which fall below the 1% threshold for maximum allowable error.